Reprint of: Dealing with dust – Some challenges and solutions for enabling solar energy in desert regions. (15th September 2017) - Boddupalli, Nibodh; Singh, Gurveer; Chandra, Laltu; Bandyopadhyay, Bibek
Graphical abstract: Highlights: Wind-induced dust deposition is a major challenge for implementing PV and CST system in desert regions. Large eddy simulation and experiment based investigations are performed for analyzing wake behind an inclined plate/mirror with stand depicting PV panel or heliostat. The observed strong flow oscillations behind PV panel or heliostat may (a) lead to localized dust deposition, (b) removal of mirror coating and (c) scratch of glass cover. Dust deposition in absorber pores of an open volumetric air receiver (OVAR) is discussed. A method is presented to deduce an acceptable operating condition of OVAR with cyclone separator, especially for desert regions. Abstract: In India, the desert regions of Rajasthan and Gujarat are preferred for installation of solar photovoltaic (PV) and concentrated solar thermal (CST) systems because of a high level of both DNI and GHI components of solar radiation. However, such regions pose substantial challenges in terms of dust, a high ambient temperature and scarcity of water. This paper is an attempt to address issues related to the deposition of dust (a) on a mirror with stand depicting PV panel or heliostat in the wake of a similar geometry and (b) in the porous absorber of an open volumetric air receiver (OVAR). A detailed insight to the wake-region behind an inclined flat-plate or heliostat is provided based on analysis and experiment. These indicate possible measures such as modification of the geometry of collectors to mitigate the problem of dust deposition. Also, the use of a cyclone separator with defined parameters based on a decision variable has been suggested for reliable operation of an OVAR. These problems being generic in nature, similar strategies are expected to be applicable in other desert regions subject to their specific conditions.